Research on Current Development, Impact and Future Exploration of China’s New Energy Vehicles in Northeast China - Wang, Zihan (Transactions on Economics, Business and Management Research, 2024)
China’s new energy vehicle (NEV) market has experienced rapid growth in recent years, driven by the national “double carbon” strategy and the goal of carbon neutrality by 2050. The Northeast region, as a key industrial base in China, holds unique advantages and potential for the development of the electric vehicle (EV) industry. It is imperative for the region to align with national strategies and intensify research on EVs to accelerate the country’s overall development. This paper begins by analyzing the current status of the EV market in the Northeast region. Through a regional case study, it identifies various challenges, including low consumer acceptance, inadequate technological innovation, insufficient charging infrastructure, and policy support gaps. Feasible solutions are proposed to address these challenges. These include enhancing technical research to optimize battery performance in low temperatures, fostering synergy within the industry chain, expanding charging facilities to meet market demand and improve consumer acceptance, and enhancing policy support. The paper aims to contribute to the healthy development of the NEV market in Northeast China and support China’s sustainable development goals. It offers actionable insights and recommendations for policymakers and industry stakeholders in the Northeast region and nationwide, facilitating the refinement of strategies to drive the growth of the EV industry.